No Smoking Here: Examining Reasons for Noncompliance With a Smoke-Free Policy in a Large University - Jancey, Jonine; Bowser, Nicole; Burns, Sharyn; Crawford, Gemma; Portsmouth, Linda; Smith, Jennifer (Society for Research on Nicotine and Tobacco, 2014)
Introduction: A large Australian university introduced a campus-wide smoke-free policy in 2012. Almost 1 year after implementation, reasons for noncompliance among people observed smoking on campus were examined. Methods: Six smoking locations on campus were identified after a campus-wide audit of smoking indicators (i.e., discarded cigarette butts packets and people observed smoking). At these locations, those observed smokers were interviewed. Interview responses were examined to elicit underlying themes. Results: Fifty people were seen smoking during the observation period. Those smokers interviewed comprised staff (27%) and students (73%) aged between 18 and 24 (45.9%). The majority of the students were international students (51.8%). All respondents acknowledged their awareness of the smoke-free policy. Five explanatory themes for noncompliance emerged: defiance against the policy’s perceived threat to self-governance; inconvenience to travel off campus to smoke; smoking as a physiological necessity; unintentional noncompliance through unawareness or confusion of policy boundaries; and ease of avoidance of detection or exposing others to cigarette smoke. Conclusions: Creating a culture of compliance at the University remains a significant challenge, especially considering the size of the campus, the high proportion of international students, and the logistics associated with monitoring smoking behavior in outdoor areas and on-campus student housing.